Elements of a subject-centered education model in occupational therapy education - Musick, Lauren M., author; Hooper, Barbara, advisor; Wood, Wendy, committee member; Jennings, Louise, committee member (Colorado State University. Libraries, 2015)
For two decades, scholars have urged the occupational therapy profession to prioritize placing occupation at the center of curricular designs and educational activities in order to advance occupational science and therapy (e.g., Yerxa, 1998; Whiteford & Wilcock, 2001). Subject-centered education has been proposed as one model for occupational therapy education (Hooper, 2006, 2010). However, the elements of the model and their transactions required further empirical development. Elements included the subject of occupation, other topics, and a community of knowers (Palmer, 1998). Video data were collected from U.S. occupational therapy and occupational therapy assistant programs as part of a larger study by Hooper, Krishnagiri, Price, Bilics, Taff, and Mitcham (in press) and secondarily analyzed. The thematic analysis identified which elements of a subject-centered model were present and described the interactions between elements. A reconstructed narrative of each program's video helped to illustrate the major findings. All elements of the subject-centered model seemed to be present, however interactions were more prevalent than individual elements. For instance, occupation was most often taught in relation to topics and people. Perhaps because of its complexity, occupation was rarely taught on its own and seemed a challenge to teach. The model of subject-centered education provided a valuable conceptual framework for identifying how occupation was taught and learned in the classroom.
Keywords: occupation; occupational therapy; occupation-centered; subject-centered education; thematic analysis